The valuation of Shares and the efficient-markets theory - Firth, Michael Arthur (London : Macmillan, 1977)
This book examines the reasonably critical surveys of the developments within the various specialist areas of business finance and accounting.
Includes bibliographical references and index.
osa; 11/07/18
Loans
Keywords: Investments; Capital assets pricing model; Stock exchanges; Corporations